Dissecting the structural organization, recruitment and activation mechanisms of centrosomal γ-TuRCs - Hofer, Florian W.; Würtz, Martin; Gao, Qi; Vermeulen, Bram J. A.; Schiebel, Elmar; Pfeffer, Stefan (Cytoskeleton, 2025)
Visualizing human centrosomes using cryo-electron tomography revealed the native structure and molecular organization of γ-tubulin ring complexes (γ-TuRCs). γ-TuRCs localized to two distinct centrosomal pools, one in the pericentriolar material (PCM) and another in the centriole lumen, which is released during mitosis. All detected γ-TuRCs were associated with the tetrameric adaptor protein NEDD1. Within the PCM, binding to the centrosomin (CM1) motif of the microcephaly protein CDK5RAP2 in different patterns correlates with conformational changes of γ-TuRCs. In the centriole lumen, the augmin complex anchors γ-TuRCs to the inner scaffold. These observations provide key insights into how the structural organization of γ-TuRCs and regulatory factors collectively govern the spatial and temporal control of microtubule nucleation in centrosomes.
Gesehen am 01.09.2025